Giant unilamellar vesicles (GUVs) as a new tool for analysis of caspase-8/Bid-FL complex binding to cardiolipin and its functional activity - Jalmar, O (Nature Publishing Group, 2010)
Cardiolipin (CL) has recently been shown to be both an anchor and an essential activating platform for caspase-8 on mitochondria. These platforms may be at the mitochondrial contact sites in which truncated Bid (tBid) has been demonstrated to be located. A possible role for CL is to anchor caspase-8 at contact sites (between inner and outer membranes), facilitating its self-activation, Bid-full length (FL) cleavage, tBid generation (and Bax/Bak activation and oligomerization), mitochondrial destabilization and apoptosis. We have developed an in vitro system that mimics the mitochondrial membrane contact site platform. This system involves reconstituting caspase-8, Bid-FL and CL complexes in giant unilamellar vesicles (GUVs). We first validated the system by flow cytometry analysis of light-scattering properties and nonyl acridine orange staining of their CL content. Then, we used flow cytometry analysis to detect the binding of active caspase-8 to CL and the subsequent truncation of bound Bid-FL. The tBid generated interacts with CL and induces GUV breakage and partial re-vesiculation at a smaller size. Our findings suggest an active role for mitochondrial membrane lipids, particularly CL, in binding active caspase-8 and providing a docking site for Bid-FL. This phenomenon was previously only poorly documented and substantially underestimated.